Estratificación socioeconómica del uso de los prefijos re- y super- en los jóvenes de Bogotá: acercamiento a un estudio diacrónico - Molina Ríos, Juliana Angélica; Aguirre Londoño, John Jairo; Romero Chala, Bibiana (Colombian Applied Linguistics Journal, 2015)
In young people’s speech, the reiteration of certain idiomatic expressions as constitutive of their identity and membership in a particular group is a common occurrence. This phenomenon is not distant to young people in Bogotá, in which they constantly use appreciative morphemes such as re- and super-. However, six years later, data was collected again by means of the same instrument employed in 2007. Therefore, this article presents a diachronic comparison between the data found in 2007 and 2013 in which both the frequency in use of these morphemes (re- and super-) and the social variable of socioeconomic stratification are considered. The general results show different trends in the three different socioeconomic levels. In the low levels, in 1 and 2, as established in Colombia, there was a significant increase in the use of the prefix re- in the year 2013 in comparison to 2007; in the middle levels, 3 and 4, also presented an important increase in the use of the morpheme super- in 2013; and, in the high levels, 5 and 6, in 2013, there was a decrease of the use of the prefix re-, but the use of the prefix superincreased meaningfully. In conclusion, it is evident that young people in Bogota continue using the above mentioned prefixes; although, there are variations in their use according to the socioeconomic level they belong to.